Война и мир: роман / Л. Н. Толстой - Толстой Лев Николаевич (100 Главных Книг, 2015)
Экземпляры: ф.19 (20151225) / Инвентарный номер: 52449 / Цена: 225.50. / Сис.шифр: Р1 / Авт.знак: Т 53 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)1